The cosolvent-dependent assembly of a family of three blue fluorescent lead(ii)-coordination polymers with 5-amino-2,4,6-tribromoisophthalic acid - Zhang, Kou-Lin; Chang, Yan; Zhang, Jing-Bo; Deng, Ye; Qiu, Ting-Ting; Li, Liang; Ng, Seik Weng (Royal Society of Chemistry, 2012)
By modulating the synthetic strategy based on changing the cosolvent in the synthesis, the aqueous medium assembly of lead(ii) with H 2ATBIP in the presence of different cosolvents, N,N-dimethylacetamide (DMA), methanol (CH 3OH) or N,N-dimethylformamide (DMF), leads to a family of three lead(ii) coordination polymers: [Pb(ATBIP)(H 2O) 2] ·2H 2O (1), [Pb(ATBIP)(H 2O)(CH 3OH)] ·H 2O (2) and [Pb(ATBIP)(H 2O)(DMF)]·H 2O (3) [H 2ATBIP = 5-amino-2,4,6-tribromoisophthalic acid]. Complex 1 exhibits an interesting double chain structure with [Pb 2(OH 2) 2] as the secondary building unit (SBU), which further assembles into a 3D supramolecular framework through the C-Br⋯Br halogen bonds and hydrogen bonds. Furthermore, the discrete water octamer (H 2O) 8 is found. The cosolvents, DMF and CH 3OH, which simultaneously act as the coordinated small molecules, have significant influences on the formation of different crystalline architectures. Complex 2 features a 2D network constructed by the 2 1 helical carboxylate-bridged Pb(ii) chains [Pb 2(COO) 2] n (SBUs) linked by the ligand ATBIP 2-. The intralayer C-Br⋯Br halogen bond is found and a 3D supramolecular framework is formed by the interlayer hydrogen bonds. Complex 3 crystallizes in the chiral space group P4 12 12 and possesses a 2D (4,4)-homochiral layer built from the centrosymmetrical SBU [Pb 2(COO) 2] bridged by the ligand ATBIP 2-. The interlayer hydrogen bonds further extend the chiral layers in 3 into a 3D supramolecular homochiral framework. The coordination modes of the ligand ATBIP 2- are greatly dependent on the cosolvents. Complex 3 loses crystallinity in the air and forms the material [Pb(ATBIP)(DMF)] (3A). Thermal stability and solid state fluorescent properties of 1, 2 and 3A have been studied. The second harmonic generation (SHG) property of 3A is also studied. © 2012 The Royal Society of Chemistry.